การจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษระดับประกาศนียบัตรวิชาชีพ ของวิทยาลัยอาชีวศึกษาเอกชน ในเขตราชเทวี - คงคาชาติ, สุดารัตน์; ศิรินุพงศ์, ภานุวัฒน์ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อศึกษาการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษ ระดับประกาศนียบัตรวิชาชีพ ของวิทยาลัยอาชีวศึกษาเอกชน ในเขตราชเทวี ตามความคิดเห็นของครูผู้สอนวิชาภาษาอังกฤษและนักเรียนใน 5 ด้าน คือ ด้านอาคารสถานที่ ด้านการจัดการเรียนการสอนด้านการจัดกิจกรรมนักเรียนด้านสังคมกลุ่มเพื่อน และด้านการให้บริการกลุ่มตัวอย่างเป็นครูผู้สอนรายวิชาภาษาอังกฤษระดับประกาศนียบัตรวิชาชีพในวิทยาลัยอาชีวศึกษาเอกชนในเขตราชเทวี จำนวน 18 คน นักเรียนระดับชั้นประกาศนียบัตรวิชาชีพปีที่ 1-3 ของวิทยาลัยอาชีวศึกษาเอกชนในเขตราชเทวี จำนวน 327 คน และผู้บริหารวิทยาลัยจำนวน 2 คน เครื่องมือที่ใช้เป็นแบบสอบถามเกี่ยวกับการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษ ระดับประกาศนียบัตรวิชาชีพ ของวิทยาลัยอาชีวศึกษาเอกชน สำหรับครูผู้สอนวิชาภาษาอังกฤษและสำหรับนักเรียน มีค่าความเชื่อมั่น 0.92 และ 0.96 ตามลำดับ และแบบสัมภาษณ์ผู้บริหารวิทยาลัยเกี่ยวกับแนวทางการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษ ระดับประกาศนียบัตรวิชาชีพของวิทยาลัยอาชีวศึกษาเอกชน และทำการวิเคราะห์ข้อมูลโดยใช้ ค่าร้อยละ ค่าเฉลี่ย และค่าความเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1. ครูผู้สอนวิชาภาษาอังกฤษให้ความคิดเห็นเกี่ยวกับการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษอยู่ในระดับมากทุกด้านโดยเรียงลำดับค่าเฉลี่ยจากมากไปหาน้อย คือ ด้านสังคม กลุ่มเพื่อน ด้านการจัดการเรียนการสอนด้านการจัดกิจกรรมนักเรียน ด้านอาคารสถานที่และด้านการให้บริการ ตามลำดับ 2. นักเรียนให้ความคิดเห็นเกี่ยวกับการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษ อยู่ในระดับมากทุกด้าน โดยเรียงลำดับค่าเฉลี่ยจากมากไปหาน้อย คือ ด้านการจัดการเรียนการสอน ด้านการจัดกิจกรรมนักเรียน ด้านอาคารสถานที่ ด้านสังคม กลุ่มเพื่อน และด้านการให้บริการ ตามลำดับ 3. แนวทางในการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษ จากการสัมภาษณ์ผู้บริหารวิทยาลัยพบว่า 3.1 แนวทางในการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษด้านอาคารสถานที่ของวิทยาลัยอาชีวศึกษาเอกชน เนื่องจากวิทยาลัยไม่มีห้องปฏิบัติการทางภาษาในการจัดการเรียนการสอนรายวิชาภาษาอังกฤษโดยตรงดังนั้นห้องเรียนที่ใช้จัดการเรียนการสอนภาษาอังกฤษควรมีเครื่องขยายเสียง เครื่องเล่นซีดี เครื่องคอมพิวเตอร์ เครื่องโปรเจคเตอร์ และจอฉายโปรเจคเตอร์ 3.2 แนวทางในการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษด้านการจัดการเรียนการสอนของวิทยาลัยอาชีวศึกษาเอกชน คือควรมีการประเมินครูผู้สอนวิชาภาษาอังกฤษเป็นระยะ ควรมีการจัดการเรียนการสอนรายวิชาภาษาอังกฤษทั้งในหลักสูตรและการสอนเสริมโดยจัดตั้งเป็นการอบรมหลักสูตรภาษาอังกฤษสำหรับนักเรียนและบุคคลภายนอกได้มีโอกาสเข้ามาศึกษา รวมทั้งมีครูผู้สอนวิชาภาษาอังกฤษชาวต่างชาติที่ใช้ภาษาอังกฤษเป็นภาษาหลัก 3.3 แนวทางในการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษด้านการจัดกิจกรรมนักเรียนของวิทยาลัยอาชีวศึกษาเอกชน ควรมีการจัดกิจกรรมชมรมภาษาอังกฤษ กิจกรรมหน้าเสาธง กิจกรรมวันคริสต์มาส เป็นต้น 3.4 แนวทางในการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษด้านสังคม กลุ่มเพื่อนทั้งกลุ่มเพื่อนนักเรียน เพื่อนครู ผู้บริหารและกลุ่มวิทยาลัยอาชีวศึกษาเอกชนด้วยกัน ควรกำหนดนโยบายของวิทยาลัยให้ครูผู้สอนทุกรายวิชามีความรู้ด้านภาษาอังกฤษเพื่อนำไปสอนสอดแทรกในการเรียนการสอนในรายวิชาต่างๆ และควรมีความร่วมมือของผู้บริหารระหว่างวิทยาลัยเพื่อร่วมกันจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษทั้งภายในและภายนอกวิทยาลัย 3.5 แนวทางในการจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษด้านการให้บริการของวิทยาลัยอาชีวศึกษาเอกชนควรจัดสรรงบประมาณการให้บริการด้านภาษาอังกฤษ เช่น งบประมาณสำหรับการเข้าค่าย English Camp การเรียนเสริมภาษาอังกฤษ การจ้างครูผู้สอนวิชาภาษาอังกฤษชาวต่างชาติที่ใช้ภาษาอังกฤษเป็นภาษาหลักเป็นต้น คำสำคัญ : การจัดการสภาพแวดล้อมในการเรียนภาษาอังกฤษระดับประกาศนียบัตรวิชาชีพ วิทยาลัยอาชีวศึกษาเอกชน ABSTRACT The researchaimed to study the environmental management contributing to learning English atprivate vocational colleges inRatchathewi district, based on the opinions of English teachers and students in five aspects: physical facilities, learning management, student activities, peer relationships and services. The samples of this study consisted of eighteen English teachers, teaching vocational diploma students at private vocational colleges in Ratchathewi district, three hundred and twenty-seven vocational students studying in the first to the third yearat private vocational colleges in Ratchathewi district and two college administrators. The research tools were included five rating scale questionnairesrelated toenvironmental management contributed English learning at private vocational colleges in Ratchathewi district for English teachers and students. The reliability of the questionnaire was 0.92 and 0.96 respectively. There was also an interview question form for the collegeadministrators regarding the management of the English learning at private vocational colleges.The statistics for data analysis includedpercentage, mean, and standard deviation. The results of theresearch were as follows: 1. TheEnglish teachers’ opinions on the environmental management contributing to learning English in five aspects were in high level. Sort by descending order as follows :peer relationships, learning management, student activities, physical facilities, and services. 2. The students’ opinionson the environmental management contributing to learning English in five aspects were in high level. Sort by descending order as follows :learning management, student activities, physical facilities, peer relationships and services. 3. The guidelines of the environmental management contributing to learning English from interviewing two college administratorswere found that: 3.1 The guidelines of the environmental management contributing to learning English in physical facilities. The college that does not have a language laboratory for teaching English, we should provide an amplifier, a CD player, a Computer, a Projector, and a projector screen in English classes. 3.2 The guidelines of the environmental management contributing to learning English in learning management. English teachers should be evaluated. The English course should be taught in both in the curriculum and supplementary teaching like tutoring for students and other people who wants to learn English. And we should providenative English teachersteaching in English classes. 3.3 The guidelines of the environmental management contributing to learning English in student activities. English club, English public speaking in the mornings, Christmas activities should be provided. 3.4 The guidelines of the environmental management contributing to learning English in peer relationships. College policy should be provided such as integrating English language to teach in others subjects. There should also be an collaboration between college administrators to manage the learning English both inside and outside the college. 3.5 The guidelines of the environmental management contributing to learning English in services. We should allocate a budget for English language services such as English Camp, hiring native English teachers and so on. Keywords : Environmental Management for Learning English, Vocational Certificate Atprivate Vocational Colleges